Old books, new technologies - Mckitterick, David. (Cambridge)
x, 286 s.
Keywords: "As we rely increasingly on digital resources, and libraries discard large parts of their older collections, what is our responsibility to preserve 'old books' for the future? David McKitterick's lively and wide-ranging study explores how old books have been represented and interpreted from the eighteenth century to the present day. Conservation of these texts has taken many forms, from early methods of counterfeiting, imitation and rebinding to modern practices of microfilming, digitisation and photography. Using a comprehensive range of examples, McKitterick reveals these practices and their effects to address wider questions surrounding the value of printed books, both in terms of their content and their status as historical objects. Creating a link between historical approaches and the technologies of the future, this book furthers our understanding of old books and their significance in a world of digital technology." --